Oxford new syllabus primary Mathematics workbook 5A - Yee, Dr foong pui (Karachi : Oxford university press, 2019)
The Oxford New Syllabus Primary Mathematics Workbook 5A is a companion workbook for Oxford New Syllabus Primary Mathematics Book 5. It provides additional exercises and activities to reinforce and deepen students$1 (Bunderstanding of the concepts introduced in the main textbook. Designed for primary school students, typically in their fifth year, this workbook focuses on applying mathematical skills in a variety of contexts to improve fluency, problem-solving abilities, and critical thinking.s
Keywords: Mathematics : Textbook